2015
DOI: 10.1111/jre.12335
|View full text |Cite
|
Sign up to set email alerts
|

Tanshinone IIA treatment alleviated the rat gingival connective tissue overgrowth induced by cyclosporine A

Abstract: Cyclosporine A enhanced gingival fibrous overgrowth via upregulation of the TGF-β1 and TIMP-1 expression, and downregulation of MMP-1 expression. Tan IIA can effectively prevent cyclosporine A-induced gingival fibrous overgrowth in rats by downregulating TGF-β1 and TIMP-1 expression, and upregulating MMP-1 expression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 40 publications
(89 reference statements)
0
4
0
Order By: Relevance
“…The pharmacological and therapeutic properties of Tan-IIA in the cardiovascular system have attracted interest ( 12 ). A previous study showed that Tan-IIA treatment alleviated rat gingival connective tissue overgrowth induced by cyclosporine A ( 13 ). Emerging experimental investigations and clinical trials have demonstrated that Tan-IIA prevents cardiac injury, hypertrophy and atherogenesis through estrogen receptor-α-induced oxidative stress ( 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…The pharmacological and therapeutic properties of Tan-IIA in the cardiovascular system have attracted interest ( 12 ). A previous study showed that Tan-IIA treatment alleviated rat gingival connective tissue overgrowth induced by cyclosporine A ( 13 ). Emerging experimental investigations and clinical trials have demonstrated that Tan-IIA prevents cardiac injury, hypertrophy and atherogenesis through estrogen receptor-α-induced oxidative stress ( 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…36 In addition, it was not observed in this study that the cyclosporine A administration altered the TGFβ1. Previous studies have shown an ambiguous effects of the cyclosporine A on TGFβ1 expression since it was showed that the cyclosporine A increased the TGFβ1expression in inflamed gingiva, 37 and reduced the TGFβ1expression in human lung fibroblasts. 38 This dual effect of the cyclosporine A observed in these different inflammatory conditions may be the reason of the absence of the interference of this drug on the TGFβ1expression in the model used in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Except for the suppressive effects on TIMP1 and TIMP4 via the induction of miR-618, the direct interaction between TAN and TIMPs is also widely reported. For instance, the study by Ma et al (2016) showed that TAN treatment alleviates the rat gingival connective tissue overgrowth via the inhibition of TIMP1. Moreover, the study by Tsai (2011) indicated that TAN can also attenuate high glucoseinduced collagen synthesis via by suppressing TIMP4 level in CFs.…”
Section: Discussionmentioning
confidence: 99%
“…Yang et al (2015) indicated that TAN exerts antifibrotic effects in myocardial tissues by inducing the level of miR-29b. Moreover, TAN also shows suppressive effects on TIMP family members such as TIMP1 (Ma et al, 2016) and TIMP2 (Tsai, 2011). Thus, TAN is a promising cardioprotective compound, and its antifibrotic effect may be closely related to the function of miRs.…”
Section: Introductionmentioning
confidence: 96%